(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The paper presents attempts to main focus on politicallife of Kengal Hanumanthaiah’s. The paper is also places of attention theparticipation of Kengal Hanumanthaiah in the independence friendship and hisrole in the fusion of Karnataka. The paper represents Kengal Hanumanthaiah’sposition in Politics, the managerial dream of Kengal Hanumanthaiah and how thechronological and spatial dimensions got interlinked with politics during hisperiod. The main objective of this paper is to discuss the political and socialvision of Kengal Hanumanthaiah in Karnataka.